STRATEGI MEMBANGUN LINGKUNGAN BELAJAR BERBASIS NILAI QUR'ANI MELALUI MANAJEMEN PENDIDIKAN ISLAMI (Studi Kasus di Taman Pendidikan Al-Qur'an Baitur Rohman Sidoarjo) - syafa'at, wahyu; Hadi, Didik Gatot Pranoto; Wasiah, Dwi Ajeng Sura; Yulistianintyas, Devi Ayu (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
The strategy for developing a learning environment based on Qur'anic values is a crucial aspect of Islamic education, especially in institutions like Taman Pendidikan Al-Qur'an. This study aims to analyze the implementation of Islamic education management in creating a learning environment that fosters character development based on Qur'anic values at Taman Pendidikan Al-Qur'an Baitur Rohman Sidoarjo. Using a qualitative approach with a case study method, data collection involved in-depth interviews, direct observations, and document analysis with administrators, teachers, and students. The findings indicate that effective management strategies include planning programs based on Qur'anic values, implementing structured learning activities, and conducting regular evaluations to measure program success. The conclusion of this study is that the comprehensive application of Islamic education management is capable of creating an educational environment conducive to the development of students' character, not only in religious aspects but also in enhancing the quality of social interactions and critical thinking skills. This study emphasizes the importance of holistic Islamic education management to support the formation of a Qur'anic generation with integrity.